The Wikipedia Network of Mathematicians - Chen,B; Lin,Z; Evans,T (2019)
This is data used in the paper "Analysis of the Wikipedia Network of Mathematicians". The data is taken from three snapshots of Wikipedia, taken in 2013, 2017 and 2018. It contains the raw Wikipedia data used as our source as well the results of our processing. Includes are edgelists, networks of the largest comopnent in graphml format, and tables of data on the nodes (the mathematicians). We have also included an appendix for the EPJ version of the paper, mathematiciansEPJappendix.pdf. However a complete version of this work is also at arXiv:1902.07622